2017
DOI: 10.4236/jbbs.2017.711038
|View full text |Cite
|
Sign up to set email alerts
|

The Transcutaneous Vagus Nerve Stimulation Output of the NuCalm Device of Solace Lifesciences Is Found to Be a Multifractal and Therefore It Is Indicated in the Treatment of Heart Rate Variability in the Dysfunction of Autonomic Nervous System in Anxiety, Depression and Stress

Abstract: We have investigated the Nu Calm Transcutaneous Vagus Nerve Stimulation device of the NuCalm Solace Lifesciences founding that it gives a multifractal output. A diminishing fractal/multifractal HRV is consistently reported in literature as related to a serious Autonomic Nervous System (ANS) dysfunction that of course we observe in several psychological and psychiatric disorders. Therefore, we suggest the investigators to apply such a device in subjects affected from anxiety, depression and stress using the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Second, the system uses the micro current stimulation patches, a tVNS system that is placed behind each ear at the Mastoid Process. Research has shown that this device induces an increase of parasympathetic response [1]. Next, a noise-dampening headphones…”
Section: Introductionmentioning
confidence: 99%
“…Second, the system uses the micro current stimulation patches, a tVNS system that is placed behind each ear at the Mastoid Process. Research has shown that this device induces an increase of parasympathetic response [1]. Next, a noise-dampening headphones…”
Section: Introductionmentioning
confidence: 99%
“…Second, the system uses the micro current stimulation patches, a tVNS system that is placed behind each ear at the Mastoid Process. Research has shown that this device induces an increase of parasympathetic response [1]. Next, a noise-dampening headphones Those selected were divided into two groups and administered tests to evaluate the level of their anxiety and depression symptoms.…”
Section: Introductionmentioning
confidence: 99%